Bacterial lysate add‐on therapy to reduce exacerbations in severe asthma: A double‐blind placebo‐controlled trial - Boer, Geertje M.; Braunstahl, Gert‐Jan; Ploeg, Esmee K.; Zelst, Cathelijne M.; Bruggen, Alie; Epping, Guido; Nimwegen, Menno; Verhoeven, Gert; Birnie, Erwin; Boxma‐de Klerk, Bianca M.; Bruijn, Marjolein J. W.; Stadhouders, Ralph; et al. (Clinical and experimental allergy, 2021)
Background Asthma exacerbations are frequently induced by respiratory tract infections (RTIs). Bacterial lysates have been described to possess immune‐modulatory effects and reduce RTIs as well as asthma symptoms in children. However, whether bacterial lysates have similar effects in adult asthma patients is unknown. Aims To reduce asthma exacerbations by add‐on bacterial lysate therapy in adults with severe asthma and to characterize the clinical and immune‐modulatory effects of this treatment. Methods Asthma patients (GINA 4) with ≥2 annual exacerbations in the previous year were included. The intervention regimen consisted of OM‐85/placebo for 10 consecutive days per month for 6 months during two winter seasons. Primary end‐point was the number of severe asthma exacerbations within 18 months. The study was approved by the national and local ethical review board and registered in the Dutch Trial Registry (NL5752). All participants provided written informed consent. Results Seventy‐five participants were included (38 OM‐85; 37 placebo). Exacerbation frequencies were not different between the groups after 18 months (incidence rate ratio 1.07, 95%CI [0.68–1.69], p = 0.77). With the use of OM‐85, FEV1% increased by 3.81% (p = 0.04) compared with placebo. Nasopharyngeal swabs taken during RTIs detected a virus less frequently in patients using OM‐85 compared to placebo (30.5% vs. 48.0%, p = 0.02). In subjects with type 2 inflammation adherent to the protocol (22 OM‐85; 20 placebo), a non‐statistically significant decrease in exacerbations in the OM‐85 group was observed (IRR = 0.71, 95%CI [0.39–1.26], p = 0.25). Immune‐modulatory effects included an increase in several plasma cytokines in the OM‐85 group, especially IL‐10 and interferons. Peripheral blood T‐ and B cell subtyping, including regulatory T cells, did not show differences between the groups. Conclusion Although OM‐85 may have immune‐modulatory effects, it did not reduce asthma exacerbations in this heterogeneous severe adult asthma group. Post hoc analysis showed a potential clinical benefit in patients with type 2 inflammation. Seventy‐five severe asthma patients were included (38 OM‐85; 37 placebo). While intention to treat (ITT) analysis revealed no difference in exacerbation frequencies between the groups after 18 months, per protocol analysis in patients with type 2 inflammation (PPT2) showed a non‐significant decrease. Nasopharyngeal swabs detected a virus less frequently in the OM‐85 group during respiratory tract infections. Immune‐modulatory effects were seen in several plasma cytokines. To conclude, OM‐85 might be an effective add‐on therapy in severe asthma patients with type 2 inflammation.